Prevalence and Antibiotic Resistance Pattern of Staphylococcus aureus Isolated from Clinical Samples: A Cross-sectional Study (Bangladesh Journal of Medical Microbiology, 2023)
Background: Staphylococcus aureus, mainly a hospital acquired infection is responsible for many suppurative lesions and has demonstrated the ability of developing resistance to many antimicrobial agents leading to life threatening infections and long hospital stay. Objective: This study was aimed to determine the prevalence and antibiotic susceptibility profiles of Staphylococcus aureus in different clinical specimens isolated from hospital admitted patients. Methodology: This cross-sectional study was conducted from 1 January 2019 to 31 December 2019 in the Microbiology Department of Dhaka Medical College, Dhaka, Bangladesh. Pus, wound swab and blood samples were included in this study. Isolation and identification of Staphylococcus aureus was based on culture, microscopy and different biochemical tests. The antibiotic susceptibility test was done by disc diffusion method using Kirby-Bauer technique. Results: Among 275 clinical specimens 21.63% Staphylococcus aureus were isolated among which 21.93% were isolated from pus and wound swabs and 19.05% from blood samples. Most of the Staphylococcus aureus showed resistance to azithromycin and erythromycin (68.89%) followed by clindamycin (66.67%), ampicillin (40%), linezolid (31.11%), amikacin (26.67%) and teicoplanin (24.44%). Conclusion: In conclusion there is a high prevalence of Staphylococcus aureus in clinical samples of hospitalized patients and it has shown alarmingly resistance to many of common antimicrobials.Bangladesh Journal of Medical Microbiology, January 2023;17(1):29-33